2020
DOI: 10.1186/s12933-020-01041-4
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-dependent and -independent modulation of oxidative and organellar stress in the diabetic heart by glucose-lowering drugs

Abstract: Autophagy is a lysosome-dependent intracellular degradative pathway, which mediates the cellular adaptation to nutrient and oxygen depletion as well as to oxidative and endoplasmic reticulum stress. The molecular mechanisms that stimulate autophagy include the activation of energy deprivation sensors, sirtuin-1 (SIRT1) and adenosine monophosphate-activated protein kinase (AMPK). These enzymes not only promote organellar integrity directly, but they also enhance autophagic flux, which leads to the removal of dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 162 publications
(197 reference statements)
3
70
1
3
Order By: Relevance
“…In rodent models of type 2 diabetes induced by a high-fat diet and low doses of streptozotocin treatment, autophagy was shown to be activated in pancreatic β-cells [ 21 , 70 ]. With the progression of diabetes mellitus in humans and laboratory animals, the mitochondrial-specific autophagy is suppressed in many tissues and organs (pancreas, heart, skeletal muscle, eyes) [ 20 , 22 , 23 , 24 , 25 , 28 , 71 ], which may be associated with a decrease in the activation of AMPK and SIRT1 [ 72 , 73 , 74 ]. Some studies revealed that the chronically elevated level of glucose upon type I diabetes induces the accumulation of p53 protein in the cytoplasm of β-cells of the pancreas.…”
Section: Mechanisms Of the Diabetes-induced Mitochondrial Dysfunctmentioning
confidence: 99%
“…In rodent models of type 2 diabetes induced by a high-fat diet and low doses of streptozotocin treatment, autophagy was shown to be activated in pancreatic β-cells [ 21 , 70 ]. With the progression of diabetes mellitus in humans and laboratory animals, the mitochondrial-specific autophagy is suppressed in many tissues and organs (pancreas, heart, skeletal muscle, eyes) [ 20 , 22 , 23 , 24 , 25 , 28 , 71 ], which may be associated with a decrease in the activation of AMPK and SIRT1 [ 72 , 73 , 74 ]. Some studies revealed that the chronically elevated level of glucose upon type I diabetes induces the accumulation of p53 protein in the cytoplasm of β-cells of the pancreas.…”
Section: Mechanisms Of the Diabetes-induced Mitochondrial Dysfunctmentioning
confidence: 99%
“…161,162 Interestingly, metformin and SGLT2 inhibitors have been reported to activate SIRT1 that may partly be contributing to their cardioprotective and HF-ameliorating effects. 88…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…154 Furthermore, metformin and SGLT2 inhibitors activate SIRT1 and/or AMP-activated protein kinase and variably promote autophagic flux in cardiomyocytes, which may partially explain their benefits in HF. 88 On the other hand, inhibition of autophagy/mitophagy, for example, by administering 3-methyladenine targeting several variants of phosphatidylinositol 3-kinase (PI3K), and bafilomycin A1 suppressing functions of lysosome, may lead to CVD progression. 173,186 In an animal study, the antihypertrophic and antiapoptotic effects of puerarin, an isoflavone that activates autophagy, were blocked after suppression of autophagy by pretreatment with 3-methyladenine.…”
Section: Fission-and Fusion-promoting Proteinsmentioning
confidence: 99%
“…12 In addition, they cannot be ascribed to natriuretic effect, since diuretic therapy has been associated with increased risk of CVD and mortality in patients with HF. [13][14][15][16] As a consequence, accumulating evidence has been gathered in an attempt to figure out the possible underlying mechanisms of cardioprotection. In view of the rapid decline in risk of HHF, it can be speculated that the benefits of SGLT2Is are due to the direct effects on the heart itself, namely improved DCM, instead of metabolic improvement.…”
Section: Introductionmentioning
confidence: 99%